Prevalence and correlates of cyber-victimization in a nationally representative sample of South African youth - Hlatshwayo, Lerato (Department of Public Health and Family Medicine, 2025)
Cyber-victimization is defined as “the experience of aggressive behaviours while using new electronic technologies, primarily mobile phones and the internet" (Álvarez-García et al., 2015a; Smith & Steffgen, 2013). Approximately 20 to 50% of adolescents have experienced online victimization globally (Zhu et al., 2021). This is a public health concern because cyber victimization can harm the mental health of the victim thus leading to depressive symptoms such as anxiety, helplessness, distress, sadness, trauma symptoms, reduced self-esteem, feelings of isolation, fear of socialization, hopelessness, self-harm, or suicidal ideation (Hertz et al., 2015; Kim et al., 2022; Landoll et al., 2015; Mason et al., 2009). Research on the risk factors associated with cyber-victimization is relatively new and has some gaps and inconsistencies (Álvarez-García et al., 2015a; Zhu et al., 2021). This study will focus on analyzing the association of some demographic, psychological, educational, family factors and exposure to other forms of violence, with cyber-victimization, in a nationally representative sample of South African children. We aim to determine the lifetime prevalence and last-year prevalence (i.e., annual incidence) of cyber-victimization, as well as the association of cyber-victimization with its correlates, based on a nationally representative cross-sectional study of 15–17-year-old youth in South Africa.